ESTIMATION OF SUBSURFACE STRUCTURE BASED ON MICROTREMOR, BORE HOLE OBSERVATIONS AND STOCHASTIC STRONG GROUND MOTION SIMULATIONS IN PALU CITY, CENTRAL SULAWESI, INDONESIA: A VALIDATION AND SENSITIVITY STUDY ON THE 23 JANUARY 2005 (PALU) EARTHQUAKE - Pyi Soe Thein; Subagyo Pramumijoyo; Wahyu Wilopo; Agung Setianto; Kirbani Sri Brotopuspito; Junji Kiyono (Geological Engineering Department Universitas Gadjah Mada, 2015)
In this study, we investigated the subsurface structure and strong ground motion parameters for Palu City. One of the major structures in Central Sulawesi is the Palu-Koro Fault system. Several powerful earthquakes have struck along the Palu-Koro Fault during recent years, one of the largest of which was an M 6.3 event that occurred on January 23, 2005 and caused several casualties. Following the event, we conducted a microtremor survey to estimate the shaking intensity distribution during the earthquake. From this survey we produced a map of the peak ground acceleration, velocity and ground shear strain in Palu City. We performed single observations of microtremors at 151 sites in Palu City. The results enabled us to estimate the site-dependent shaking characteristics of earthquake ground motion. We also conducted 8-site microtremor array investigation to gain a representative determination of the soil condition of subsurface structures in Palu. From the dispersion curve of array observations, the central business district of Palu corresponds to relatively soil condition with Vs ≤ 300 m/s, the predominant periods due to horizontal vertical ratios (HVSRs) are in the range of 0.4 to 1.8 s and the resonant frequency are in the range of 0.7 to 3.3 Hz. Three boreholes were throughout the basin especially in Palu area to evaluate the geotechnical properties of subsurface soil layers. The depths are varying from 1 m to 30 m. Strong ground motions of the Palu area were predicted based on the empirical stochastic green’s function method. Peak ground acceleration and peak ground velocity becomes more than 0.04 g and 30 kine in some areas, which causes severe damage for buildings in high probability. Keywords: Palu-Koro fault, microtremor, bore holes, peak ground acceleration and velocity.